Analisis Undang-Undang Nomor 41 Tahun 2004 dan Hukum Islam tentang Wakaf terhadap Tugas Nazhir pada Aset Wakaf Masjid Al-Huda Kabupaten Sumedang - Aditya Yunianto; Siska Lis Sulistiani; Asep Ramdan Hidayat (Bandung Conference Series: Islamic Family Law, 2024)
Abstract. Al-Huda Mosque has not been administered in legal legality. This is due to several factors, including Nazhir as the waqf manager who was given a mandate by the Wakif has not carried out all his duties and obligations properly, resulting in problems with the sale and purchase of waqf assets. This is in conflict with Law Number 41 of 2004 Article 40 that waqf assets, among others, may not be traded and Islamic Law which has implications in Article 11 concerning the duties of nazhir. Based on this phenomenon, the problems in this study are formulated (1) How is the analysis of Law Number 41 of 2004 concerning Waqf regarding the duties of nazhir on the waqf assets of the Al-Huda Mosque in Sumedang Regency (2) How is the analysis of Islamic Law regarding the duties of nazhir on the waqf assets of the Al-Huda Mosque in Sumedang Regency. This study is a normative legal research conducted at the Al-Huda Mosque, North Sumedang District, Sumedang Regency, using qualitative research. The research approach uses a normative legal approach. There are two sources of research data used, namely: data source The results of this study are that nazhir in carrying out his duties does not fulfill his duties. Reviewed from Law Number 41 of 2004 Article 11 Nazhir only manages waqf assets and reviewed from Islamic law, the rules of fiqh which means "The actions (regulations) of government leaders towards the people are aimed at the interests and welfare of the people." This fiqh rule contains the meaning that a nazhir as a trustee must fulfill his duties. Nazhir has not fully carried out his duties, and has caused harm rather than the welfare of the people. So, nazhir in carrying out his duties has not fully fulfilled the provisions contained in Law Number 41 of 2004 Article 11 and Islamic Law. Abstrak Masjid Al-huda belum teradministrasi dalam legalitas hukum. Hal ini karena beberapa faktor, diantaranya Nazhir sebagai pengelola wakaf yang diberikan mandat oleh Wakif belum melaksanakan semua tugas dan kewajibannya dengan baik, sehingga menimbulkan permasalahan akan diperjualbelikan aset wakaf. Hal ini bersinggungan dengan Undang-Undang Nomor 41 Tahun 2004 Pasal 40 bahwa aset wakaf diantaranya tidak boleh diperjualbelikan dan Hukum Islam yang berimplikasi pada pasal 11 mengenai tugas nazhir. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan (1) Bagaimana analisis Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf terhadap tugas nazhir pada aset wakaf masjid Al-Huda Kabupaten Sumedang (2) Bagaimana analisisHukum Islam terhadap tugas nazhir pada aset wakaf masjid Al-Huda Kabupaten Sumedang. Penelitian ini termasuk penelitian yuridis normatif yang dilakukan di Masjid Al-Huda Kecamatan Sumedang Utara Kabupaten Sumedang, dengan menggunakan penelitian kualitatif. Pendekatan penelitian dengan menggunakan pendekatan yuridis normatif. Sumber data penelitian yang digunakan ada dua yaitu: sumber data Hasil dari penelitian ini adalah nazhir dalam melaksanakan tugasnya tidak memenuhi tugasnya. Ditinjau dari dalam Undang-Undang Nomor 41 Tahun 2004 Pasal 11 Nazhir hanya melakukan pengelolaan aset wakaf dan ditinjau dari hukum Islam kaidah fikih yang artinya berbunyi “ Tindakan (peraturan) pemimpin pemerintah terhadap rakyat itu bertujuan pada kepentingan dan kemaslahatan rakyatnya.” Kaidah fikih ini mengandung makna seorang nazhir sebagai pemegang amanah hendaknya harus memenuhi tugasnya. Nazhir belum sepenuhnya melaksanakan tugasnya, dan menimbulkan kemudharatan bukan kemaslahatan rakyat. Jadi, nazhir dalam melaksanakan tugasnya belum sepenuhnya memenuhi ketentuan yang terdapat dalam Undang-Undang Nomor 41 Tahun 2004 Pasal 11 dan Hukum Islam.